DBpedia linkage analysis leveraging on entity semantics - Fuchs, David (2020)
This thesis focuses on the analysis of interlinking of Linked Open Data resources in various data silos and DBpedia, the hub of the Semantic Web. It also attempts to analyse the consistency of bibliographic records related to artwork in the two major encyclopaedic datasets, DBpedia and Wikidata, in terms of internal consistency of artwork in Wikidata, which models its entries in compliance with the Functional Requirements for Bibliographic Records (FRBR), as well as the consistency of interlinking from DBpedia to Wikidata.The first part of the thesis describes the background of the topic, focusing on the concepts important for this thesis: Semantic Web, Linked Data, Data quality, knowledge representations in use on the Semantic Web, interlinking and two important ontologies (OWL and SKOS).The second part is dedicated to the analysis of various data quality features of interlinking with DBpedia. The results of this analysis of interlinking between various sources of LOD and DBpedia has led to some concerns over duplicate and inconsistent entities, but the real problem appears to be the currency of data with only half of the datasets linking DBpedia being updated at most five years before the data collection for this thesis took place (October through November 2019). It is also concerning that almost 14 % of the interlinked datasets are not available through standard Semantic Web technologies (SPARQL, dereferenceable URIs, RDF dump). The third part starts with the description of the approach to modelling artwork entities in Wikidata in compliance with FRBR and then continues with the analysis of internal consistency of this part of Wikidata and the consistency of interlinking of annotated entities from DBpedia and their counterparts from Wikidata. The percentage of FRBR entities in Wikidata found to be affected by inconsistencies is 1.5 %, but this figure may be higher due to technological constraints that prevented several queries from finishing.